Primary squamous cell carcinoma of the breast: a case report and review of literature - Seddik, Youssef (Pan Afr Med J, 2015)
Primary squamous cell carcinoma is a well known malignancy of the skin and other organs composed of squamous cells, which are normally not found inside the breast. Therefore, a primary squamous cell carcinoma of the breast is an exceedingly uncommon phenomen and the management of this type of disease is still unclear. We report the case of a 43-year-old Moroccan woman, without significant medical history, presented an infected mass of 9 cm in the left breast associated with ipsilateral axillary lymphadenopathy. The mass's surgical biopsy revealed a triple negative primary squamous cell carcinoma of the breast. She underwent a neoadjuvant chemotherapy using 5 Fluoro-Uracil and platinum. After three courses, she presented a contralateral breast progression and apparition of metastasis at D10. She received one course of a palliative chemotherapy based on weekly paclitaxel stopped because of her peformans status deterioration. She died 7 months after her admission.